The summer people - Hull, Eleanor Means (Atheneum, 1984)
Jenny reflects on the summers she and her parents have spent in a mountain summer colony where she's found all the people she's liked best and from whom she's learned to judge life, even though, as a Jew, she's never felt quite accepted.